Efficacy of Melissa officinalis L. (lemon balm) extract on glycemic control and cardiovascular risk factors in individuals with type 2 diabetes: A randomized, double‐blind, clinical trial. (10th December 2018) - Asadi, Akbar; Shidfar, Farzad; Safari, Mostafa; Hosseini, Agha Fatemeh; Fallah Huseini, Hasan; Heidari, Iraj; Rajab, Asadollah
Abstract : Melissa officinalis is a plenteous source of antioxidant flavonols and flavonoids that contain health‐promoting and antidiabetic properties, so this study was undertaken to provide the first assessment of the antidiabetic properties of hydroalcoholic extract of M .  officinalis in type 2 diabetic patients. We did a randomized, placebo‐controlled trial which included 62 patients, receiving either M .  officinalis capsules (700 mg/d; n  = 31) or the placebo ( n  = 31) twice daily for 12 weeks. There were significant differences in serum FBS ( P  = 0.007), HbA1c ( P  = 0.002), β‐cell activity ( P  = 0.05), TG ( P  = 0.04), HDL‐c (P = 0.05), hs‐CRP ( P  = 0.001), and systolic blood pressure ( P  = 0.04) between the two groups at the end of the study; but total cholesterol, LDL‐c, insulin, and HOMA‐IR showed no significant changes between the groups. In M .  officinalis group, there was a significant change in HDL‐c ( P  = 0.009) and QUICKI ( P  = 0.005) compared with baseline values. No adverse effects were observed. It seems that M .  officinalis is safe and effective in improvement of lipid profile, glycemic control, and reduction of inflammation.